Optimizing Academic Achievement of Students through Effective Leadership of Principal - Falah, Saiful; Maulana, Irwan; Izzah, Nuril (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
This study aims to analyze how the leadership of the Madrasah Aliyah Ummul Quro al-Islami principal plays a role in improving the academic achievement of its students. This research method uses a descriptive qualitative approach. Observations are used to observe phenomena in the field. Key informants in this study were the head of the madrasa, deputy head of curriculum and student affairs, homeroom teacher, subject teacher, and students. Documentation studies are used to observe documents related to research topics. Data analysis techniques include coding, thematic grouping, identifying patterns, and drawing conclusions. The results of the study found that the leadership of madrasah aliyah in increasing academic achievement was initiated by standardizing prospective madrasah heads given foundations, exemplary character development, NU values, cooperation, strengthening academic improvement programs, and the principal's desire for the role of pesantren alums in working in all fields of the profession. The results of this study can be used as a practical guide for madrasa heads in developing their leadership competencies and creating a conducive learning environment through adequate management of resources in the context of madrasah to improve student academic achievement.